The origin of drumlins at Zbójno, Central Poland - Głębicki, Piotr; Marks, Leszek (Geologija, 2009)
Drumlins at Zbójno, Dobrzyń Lakeland, are located in a channel-like terminal basin, in the proximal part of the Chrostkowo end moraines. A fragment of the drumlin field was examined in detail. The drumlins are elongated ridges, parallel to one another and to the basin margins. Their orientation is parallel to perpendicular with regard to the presumed regional direction of the ice sheet advance. The drumlins' geological structure is tripartite, including a lower till, a glaciofluvial core and a covering upper till. Georadar examination indicated the presence and extension of glaciotectonic deformations of the lower till. It is squeezed up to 3 m above its primary setting and forms protodrumlins that have not been, however, the bed bumps that stimulated a lee-side deposition. Protodrumlins are usually absent along a drumlin axis, but they occur also in pairs. They could both initiate but also terminate drumlin development when thawing appeared in the subglacial zone and the ice body was disintegrated into dead-ice blocks. Glaciofluvial cores are less deformed than the lower till: their sediments are stratified, but commonly uplifted towards a protodrumlin.